Fecal Calprotectin as a Selection Tool for Small Bowel Capsule Endoscopy in Suspected Crohn's Disease - Monteiro, Sara (2018)
Small bowel capsule endoscopy (SBCE) is a firstline examination in patients with suspected Crohn's disease (CD) after negative ileocolonoscopy. Fecal calprotectin (FC) is a noninvasive marker of intestinal inflammation. The aim of this study was to evaluate the predictive value of FC in inflammatory activity detected by SBCE in patients with suspected CD.